Anti-asthmatic property and possible mode of activity of an ethanol leaf extract of Polyscias fruticosa. (2nd August 2016) - Asumeng Koffuor, George; Boye, Alex; Kyei, Samuel; Ofori-Amoah, Jones; Akomanin Asiamah, Emmanuel; Barku, Atsu; Acheampong, Jacqueline; Amegashie, Elikplim; Kumi Awuku, Albert
Abstract: Context : Polyscias fruticosa (L.) Harms (Araliaceae) is used as a traditional remedy for asthma in Ghana. Objective : The objective of this study is to establish the anti-asthmatic property and a possible mode of activity of an ethanol leaf extract of P. fruticosa (PFE). Materials and methods : The time (min) for pre-convulsive dyspnea, and time for recovery, after sensitization with 150 μg OVA and induction of bronchospasm with 1% acetylcholine or histamine in normal, and 100, 250, and 500 mg/kg PFE-treated Dunkin Hartley guinea pigs, were recorded. Atropine (0.1 mg), mepyramine (0.1 mg), and PFE (1 mg) effect on a contractile response of 2.0 × 10 −2  μg/ml acetylcholine and 5.8 × 10 −2  μg/ml histamine on the isolated guinea pig ileum was investigated. Cytological and histological studies were conducted using guinea pig peritoneal mast cells and mesenteric cells, respectively, to establish PFE effect on compound 48/80-induced mast cell degranulation. Results : PFE (100–500 mg/kg) prolonged the onset of pre-convulsive dyspnea by 76.1–180.2% ( p  ≤ 0.01–0.001), and decreased recovery time by 71.9–78.5% ( p  ≤ 0.01–0.001). It also enhanced percentage protection against histamine-induced bronchospasm by 15.8–80.1-fold ( p  ≤ 0.05–0.01), and decreased percentage recovery time 2.5–3.3-fold ( p  ≤ 0.05–0.01). PFE significantly inhibited (60.4 ± 8.3%) contractile responses of histamine and produced significant inhibition (56–79%: p  ≤ 0.001) of mast cell degranulation. Conclusion : PFE has anti-asthmatic, antihistaminic, and mast cell stabilization effect making it useful in traditional asthma management.